Juristocracy as a challenge for social movements in the 21st century: From Pinochet‘s legacy to the asamblea constituyente? - Unterberger, Fabian (Momentum Quarterly, 2012)
Legislative politics are increasingly replaced by the inscription of elite interests in law and constitutions. Ran Hirschl (2004) terms this insulation of neoliberal policies „juristocracy“. The aim of this paper is to investigate the implications of this closure of the political- institutional system for dynamics and strategy of social movements and for their theoretical localisation. If they don’t succeed in realising their demands due to a rigid political- institutional system, diverse social movements can converge in a common call for democracy. The case study of the student protests in Chile shows how social movements contest the juristocracy inherited from the era of Pinochet with a broad alliance for democratisation. Inspired by the example of the Latin-American nuevo constituconalismo they start to argue with the necessity of a new constitution and confront the constituted power with the constituent power. This paper identifies the gap between constituent power and constituted power as the central axis of the conflict, which furthermore determines the democratic validity of a society.